Recent progress in sodium alginate based sustainable hydrogels for environmental applications - Thakur, Sourbh; Sharma, Bhawna; Verma, Ankit; Chaudhary, Jyoti; Tamulevicius, Sigitas; Thakur, Vijay Kumar (Elsevier, 2018)
Recently, there is a growing research interest in the applications and development of novel sustainable hydrogel materials in waste water treatment because of radically distinctive chemical and physical characteristics of hydrogels such as hydrophilicity, swell ability and modifiability to name a few. Hydrogels have exposed the hypernym functioning in the removal of a wide range of aqueous pollutants containing toxic dyes and heavy metal ions. A large amount of water gets incorporated in the three dimensional networks of hydrophilic structures of hydrogels. The prime objective of this review article is to render a presentation on the recent advances in the modifications of sodium alginate based hydrogels for the adsorptive removal of toxic pollutants. In addition, article also briefly gives the classification and properties of hydrogels and alginate.
Keywords: Alginate; Sodium alginate based hydrogel; Dye and metal removal; Water purification